APPLICATION OF NMR IN THE INVESTIGATION OF DYNAMIC TAUTOMERISM OF 4(3H)-QUINAZOLINONE SYSTEM - Pham Thi Thanh My; Chu Dinh Kinh; Thanh Thi Thu Thuy; Nguyen Ngoc Vinh; Nguyen Thi Phuong Chi (Universitas Gadjah Mada, 2008)
Tautomerism of 4(3H)-quinazolinone system with [(2-hydroxyphenyl)methylene]-2-(4oxoquinazolin-3(4H)-yl)acetohydrazide and N’-[(1E)-(4-hydroxy-3-methoxyphenyl)methylene]-2-(4-oxoquinazolin-3(4H)-yl)acetohydrazide as two representative compounds was investigated on the basis of 1H NMR method at coalescence with the help of line formprogramme. The dynamic parameters such as k, Ea, DG*, DH*, DS* were fully calculated with high reliability.